2018
DOI: 10.1556/2060.105.2018.4.25
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exhaustive swimming and probiotic administration in trained rats: Oxidative balance of selected organs, colon morphology, and contractility

Abstract: The duration and intensity of exercise are significant factors in oxidative, morphological, and functional changes of the gastrointestinal tract. This study aimed to investigate the effects of both exhaustive swimming and probiotic VSL#3 on rats that had been previously trained with moderate swimming. The rats were divided into four groups labeled: control (C), probiotic (P), exercise (E), and probiotic-exercise (PE). Groups P and PE were fed with probiotic mixture VSL#3. Groups E and PE had a 5-week moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Numerous researches have indicated the validity of intestinal microbiota-targeted strategies to improve training parameters and increase training capabilities, as presented in Table 1. The researches indicate the ability of intestinal microbiota to alleviate oxidative stress and exercise-induced inflammation [78][79][80]119,120]. A trial conducted by Jager et al have shown that Bacillus coagulans GBI-30 probiotic supplementation improves the anaerobic capacity measured by the Wingate Test [121].…”
Section: Impact Of the Microbiome On Exercise Capacitymentioning
confidence: 99%
“…Numerous researches have indicated the validity of intestinal microbiota-targeted strategies to improve training parameters and increase training capabilities, as presented in Table 1. The researches indicate the ability of intestinal microbiota to alleviate oxidative stress and exercise-induced inflammation [78][79][80]119,120]. A trial conducted by Jager et al have shown that Bacillus coagulans GBI-30 probiotic supplementation improves the anaerobic capacity measured by the Wingate Test [121].…”
Section: Impact Of the Microbiome On Exercise Capacitymentioning
confidence: 99%
“…Dardmeh et al [2] showed that Lactobacillus SAYINER, GÜLMEZ SABİT, GÜLMEZ Deep-frying Oil Effect on Sperm rhamnosus PB01 has a positive effect on both weight loss and reproductive hormones, significantly improving sperm motility and kinematic parameters. Numerous studies have been published using various rodent species to investigate the effects of probiotics on health [16,[32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Associations between probiotics and physical performance and plausible mechanisms underlying these actions have been addressed in animal studies, which have suggested that probiotic supplementation protects against undesirable physiological changes that may be induced by strenuous exercise. Preclinical studies have demonstrated that probiotics can improve gut barrier properties [ 61 ] and the antioxidative status [ 62 ] and attenuate inflammatory response [ 63 , 64 , 65 ] in rodents after exhaustive exercise. However, how these protective effects are associated with physical performance outcomes has not been determined.…”
Section: Probiotics As a Potential Ergogenic Aid To Enhance Physicmentioning
confidence: 99%